Effectiveness of a Drinking and Driving Campaign on Knowledge, Attitudes, and Behavior Among Drivers in Addis Ababa - Negi, Nalin Singh; Schmidt, Karen; Morozova, Irina; Addis, Tigist; Kidane, Solomon; Nigus, Asmeret; Kumar, Namrata; Mullin, Sandra; Murukutla, Nandita (Frontiers in Sustainable Cities, 2020)
Background: In Addis Ababa, Ethiopia, road traffic crashes represent a major public health challenge. Driving under the influence of alcohol (drink driving) is a risk factor for road traffic crashes. Mass media campaigns can reduce drink driving. Few studies to date evaluate the influence of anti-drink-driving campaigns on changes in knowledge, attitudes, and behaviors in low-income countries such as Ethiopia. Objective: This study aims to examine the impact of an anti-drink-driving campaign on knowledge, attitudes, and behavior around drinking and driving in Addis Ababa, Ethiopia. Methods: The “Never Drink and Drive” campaign ran on media outlets in Addis Ababa and consisted of evidence-informed messages on the consequences of drink driving. Data for this study comes from two representative household surveys conducted among a sample of adult drivers aged 18 to 55 years in Addis Ababa pre-campaign (n=721) and post-campaign (n=721). Multivariate logistic regression is used to estimate the effects of the campaign on drink-driving knowledge, attitudes, and behavior. Results: After the campaign, participants were significantly more likely to have improved knowledge and attitudes about drink driving: post-campaign participants were significantly more likely to report feeling unsafe about drink driving (OR=1.51, p < 0.05). Social norms showed a positive shift: post-campaign participants were over six and a half times more likely to report someone talked to them about drink driving (OR=6.52, p < 0.05). After the campaign, participants demonstrated improved knowledge and attitudes around drink driving laws and enforcement, including significantly more likely to agree they would be caught by police for drink driving (OR=12.66, p < 0.1). Behavior also improved—post-campaign participants reported significantly lower rates of driving soon after drinking alcohol, compared with pre-campaign participants (31% vs. 42%). Conclusion: The anti-drink-driving campaign achieved gains in knowledge, improved attitudes, and reduced drinking and driving, which can help to curb road traffic crashes in Addis Ababa. This study offers some of the first evidence that an anti-drink-driving campaign, combined with enhanced enforcement of road safety laws, can be effective in changing knowledge, attitudes, and behaviors around drink driving in low-income countries.